Knowledge, awareness, and perception of coronary heart disease (CHD) among residents in Kuantan, Pahang, Malaysia - Sumaiyah Jamaludin, Thandar Soe; Jorani, Shuhadah; Saidi, Sanisah (Elsevier Espa˜na, 2019)
Objective: This study aimed to determine the level of knowledge, awareness, and perception about CHD symptoms and risk factors among residents in Kuantan, Pahang. Methods: A cross-sectional study was conducted in 400 participants who presented at four shopping malls in Kuantan city. A convenient sampling method was used to recruit participants. A self-administered questionnaire was used in collecting data. Data were analyzed by using SPSS version 22.0. Results: Majority of the participants were Malays with mean age among 18---39 years old. Of the 400 participants, the majority had high knowledge of CHD poor awareness and poor perception of CHD. There was an association between socio-demographics and knowledge, awareness, and perception level towards CHD with p-value <0.05. Conclusion: These study findings indicated that public health promotion and intervention are needed in Kuantan, Pahang regards to knowledge and awareness of CHD symptoms and risk factors.